Chemerin/CMKLR1 Axis Promotes Inflammation and Pyroptosis by Activating NLRP3 Inflammasome in Diabetic Cardiomyopathy Rat - Xie, Yebin; Huang, Yu; Ling, Xiaoyu; Qin, Haiou; Wang, Min; Luo, Beibei (Frontiers in Physiology, 2020)
Chemerin and its receptor CMKLR1 (a G-protein-coupled receptor) are inducers of inflammation, and play an important role in diabetic cardiomyopathy (DCM). In this study, we investigated the role of the chemerin/CMKLR1 axis in mediating inflammation and cell death in DCM. Sprague–Dawley rats, treated with a high-fat diet and low-dose of streptozotocin, were used as a DCM model. CMKLR1 expression was knocked down by siRNA (CMKLR1-siRNA) to evaluate the role of CMKLR1 in DCM. Chemerin-treated H9c2 cells were used to investigate the factors acting downstream of the chemerin/CMKLR1 axis. LDH release and EthD-III staining were used to measure the ratio of cell death in vitro. CMKLR1-siRNA and siRNA against nucleotide-binding oligomerization domain-like receptors 3 (NLRP3-siRNA) were used to explore the mechanism underlying chemerin-induced inflammation and cell death. The results showed that the expression of chemerin, CMKLR1, NLRP3, pro-caspase-1, activated caspase-1, and mature IL-1β was increased in the DCM model rat. Myocardium of DCM model rats exhibited fibrosis, hypertrophy, a disorganized ultrastructure, and impaired function. Pyroptosis was observed in vivo and in vitro. Silencing of CMKLR1 in vivo attenuated the expression of NLRP3 and activated caspase-1 and IL-1β. CMKLR1-siRNA treatment attenuated cardiac inflammation, fibrosis, hypertrophy, and pyroptosis, and improved cardiac function in vivo. Silencing of either CMKLR1 or NLRP3 suppressed the levels of activated caspase-1, IL-1β, and pyroptosis; however, silencing of both CMKLR1 and NLRP3 further decreased the levels of mature IL-1β and pyroptosis. Overall, the results showed that the chemerin/CMKLR1 axis contributed to the development of DCM and that the NLRP3 inflammasome mediated the chemerin/CMLR1-induced inflammation and pyroptosis. These data indicate that silencing of the CMKLR1 gene might exert a protective effect against DCM.